Podcasting in ESL classrooms: learners' perceptions, beliefs and attitudes - Hasan, Md. Masudul (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Listening is considered as the most frequently used language skill in almost any communication, yet it is often observed to be particularly difficult, and sometimes causes anxiety and frustration among foreign and second language learners. Successful communication can be hindered without accurate understanding of the spoken message. Several research studies have suggested the use of podcast materials to develop ESL learners’ listening comprehension. This study examines ESL students’ perceptions, beliefs and attitudes towards the use of podcasts in terms of developing their listening competence. Perceptions and attitudes towards podcasts have been investigated through a survey questionnaire. The vast majority of the respondents stated that they enjoyed using podcast and that it had stimulated their interest in learning English. They also acknowledged that the use of podcasts could help improve their language skills particularly listening.